1989
DOI: 10.1111/j.1365-2125.1989.tb03538.x
|View full text |Cite
|
Sign up to set email alerts
|

CNS‐related subjective symptoms during treatment with beta 1‐ adrenoceptor antagonists (atenolol, metoprolol): two double‐blind placebo controlled studies.

Abstract: 1 Whilst a number of studies have investigated whether metoprolol and atenolol, the most widely used 31-adrenoceptor antagonists, differ with regard to CNS-related subjective symptoms, few placebo-controlled studies using standardised questionnaires have been performed. 2 In the present report, the findings of two randomised, double-blind, cross-over studies in healthy volunteers are presented. The subjects were treated with placebo and atenolol (100 mg once daily) (Study 1) and metoprolol (100 mg once daily) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The general adverse effects (AEs) of propranolol include nausea, vomiting, diarrhea, and other gastrointestinal symptoms. Severe adverse events include inhibition of cardiac function, Raynaud's phenomenon, aggravating bronchospasm, hyperkalaemia, depression, somnolence, and insomnia, which can result in serious consequences [2, 47]. At present, there are few reports on the risk factors of AEs in infants receiving oral propranolol; moreover, the long-term side effects of propranolol in infants are unknown [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…The general adverse effects (AEs) of propranolol include nausea, vomiting, diarrhea, and other gastrointestinal symptoms. Severe adverse events include inhibition of cardiac function, Raynaud's phenomenon, aggravating bronchospasm, hyperkalaemia, depression, somnolence, and insomnia, which can result in serious consequences [2, 47]. At present, there are few reports on the risk factors of AEs in infants receiving oral propranolol; moreover, the long-term side effects of propranolol in infants are unknown [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Bardage et al [47] demonstrated that hypertensive patients had signi cantly lower quality of life, with lower health-related quality of life (HRQL) and 36-item short form questionnaire (SF-36) scores. Previous studies explained that hypertensive individuals have reported lower social and psychological functioning [50,51] and have been associated with symptoms [52,53] and/or side effects of antihypertensive medication [54,55] such as headache, dizziness, depression, anxiety, and tiredness.…”
Section: Discussionmentioning
confidence: 99%
“…The MSE‐P was originally designed to measure CNS‐related symptoms in association with cardiovascular drugs ( Dahlöf et al . 1989 ; Dimenäs et al . 1989a , b).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, contentment provides a measure of the impact of the treatment method on the individual. Although the questionnaire has been used in patients with hypertension and migraine ( Dimenäs et al . 1989a , b; Dahlöf and Dimenäs 1995 ) to our knowledge it has never been applied to patients with OSA.…”
Section: Introductionmentioning
confidence: 99%